Insect Nicotinic Acetylcholine Receptors - Thany, Steeve Herv.̌ (Advances in Experimental Medicine and Biology, 2010)
The aim of this book is to summarize our understanding on the insect nicotinic acetylcholine receptors. This area of research received great impetus from the identification of the first subunit sequences to be used as neonicotinoid insecticide target sites. Although a book of this nature can provide the details only of commonly published results, it is hoped that it may provide a useful guide to the newcomer to the field as well as to point out some of the future challenges. For example, we need to determine the precise subunit nomenclature of insect nicotinic receptors. This nomenclature varies amongst species and this led to some of the early confusion that persists. We need to be precise in identifying the subunit composition of native insect nicotinic receptor subtypes, their functional properties and physiological roles.